Natural noise affects conspecific signal detection and territorial defense behaviors in songbirds. (5th July 2021) - Reed, Veronica A; Toth, Cory A; Wardle, Ryan N; Gomes, Dylan G E; Barber, Jesse R; Francis, Clinton D
Abstract: Recent research suggests that anthropogenic noise can substantially alter animal behavior. Although there are many sources of natural background noise, the relative influence of these sounds on behavior has received much less attention. Using landscape-scale playbacks of rushing rivers and crashing ocean surf, we investigated how habitat appropriate natural noise alters territorial defense behaviors in lazuli buntings ( Passerina amoena ) occupying riparian areas and spotted towhees ( Pipilo maculatus ) in riparian and coastal areas when exposed to simulated intruder song. We also incorporated naturally occurring cicada noise as an acoustic source influencing lazuli bunting behavior. Both songbird species possess songs that share substantial spectral overlap with low-frequency, water-generated noise, and lazuli bunting song shares an additional high-frequency overlap with cicada calls. Thus, there is potential for background acoustic conditions to mask conspecific signals. We found that detection and discrimination of conspecific playback occurred more slowly for both species as background sound levels increased. Lazuli buntings also exhibited complex flight behavior in noise, suggesting they respond differently depending on the amplitude and type of background noise (with versus without cicada calls). Our results suggest natural noise can impair territorial defense behaviors in songbirds, highlighting natural soundscapes as an under-appreciated axis of the environment. Abstract : Human-generated noise affects animal behavior in numerous ways, yet how natural noise influences behavior remains largely unknown. We found that increases in natural noise conditions (i.e., experimental ocean surf or river noise, and/or free-living cicada chorus noise) alter signal detection and songbird defensive behaviors in response to simulated intruder song, similar to the effects of human-generated noise. Our results suggest that interference from natural background noise could be a prevailing evolutionary driver in animal communication.